Is Mini Nutritional Assessment a Good Prognostic Tool of Activities of Daily Living in Ederly? - Mojde Mirarefin; Farshad Sharifi; Neda Nazari; Hossein Fakhrzedeh; Maryam Ghaderpanahi; Zohre Badamchizade (University of Social Welfare & Rehabilitation Sciences, 2009)
Objectives: The aims of this study were to investigate the association of Mini-Nutritional Assessment and activities of daily living as well as examining Mini Nutritional Assessment as a good prognostic tool ofactivities of daily living in elderly residents of nursing home. Methods & Materials: In a cross-sectional study, among 1200 recorded files, 247 subjects completed Mini Nutritional Assessment and Barthel index questionnaire. The relations between studied variables were assessed using Pearson and spearman correlation. These relations were confirmed by adjusted regression model. Results: 130 elderly had Mini Nutritional Assessment≥24.5 and 102 had Mini Nutritional Assessment<23.5. Mini Nutritional Assessment and BI were positively correlated (r=0.26, P<0.001). In an age- and sex-adjusted model, Barthel index is associated significantly with age (P<0.006), Body Massive Index I (P<0.009), and MNA (P<0.001). Conclusion: Mini Nutritional Assessment can be a good predictor ofdaily living activities in elderly residents of Kahrizak Charity Foundation (KCF).